An implementation of Pentaho in reporting management module - Rumi, Arztrie Delailah (2008)
Reporting Management Module is one of SCAN Associates research and development team projects in order to find the most suitable and effective ways to develop the enhancement of the reporting module previous system. The current system’s constraints including limited option in data visualization and also data calculation has effect the productivity of Security Analyst. The research of Pentaho implementation in this Reporting Module should be able to overcome the constraints mentioned. The system is a web based system and develops using JAVA with MySQL as its database. RUP has been chosen as the software development model and UML as the software technique. The analysis and design of this system is using the Scan Associates standard and guideline. The deliverables for this project includes the Software Requirement Specification (SRS) and Software Architecture Design (SAD). The Reporting Management Module is expected to provide a fast and efficient Reporting Management Module in order to improve the productivity of Security Analyst. It is highly hope that this module would be one of the effective ways to improve the company’s quality.